Association of Alanine Aminotransferase With Different Metabolic Phenotypes of Obesity in Children and Adolescents: The CASPIAN-V Study - Kelishadi, Roya; Hemati, Zeinab; Qorbani, Mostafa; Motlagh, Mohammad Esmaeil; Djalalinia, Shirin; Ahadi, Zeinab; Shafiee, Gita; Mahdavi Gorabi, Armita; Rastad, Hadith; Ziaodini, Hasan; Daniali, Seyede Shahrbanoo; Heshmat, Ramin (Frontiers in Endocrinology, 2020)
Aim: To determine the association of alanine aminotransferase with different metabolic phenotypes of obesity in a nationally- representative sample of Iranian children and adolescents. Methods: This national study was conducted in the framework of the fifth survey of a national surveillance program entitled Childhood and Adolescence Surveillance and Prevention of Adult Non-communicable Disease study. Participants consisted of 4200 subjects aged 7-18 years, who were recruited by multistage random cluster sampling from 30 provinces in Iran. They were categorized to normal weight and obese groups and in each group those with and without MetS components. Results: Overall, 3,843 of participants completed the survey (response rate: 91.5%). Their mean (SD) age was 12.58 (3.15) years; 52.6% were boys, and 72.7% lived in urban areas. Mean of alanine aminotransferase (ALT) in subjects with abdominal obesity and general obesity was 8.81 (95% CI: 7.99- 9.62) (IU/L) and 8.87 (95% CI: 7.28- 10.46) (IU/L), respectively. According to the adjusted model, one unit increment in ALT increased odds of being metabolically non-healthy obese (MNHO) by 2% compared to metabolically healthy non-obese (MHNO). (adj.OR (95% CI): 1.02 (1.01-1.04)). Also, subjects in the third and fourth quartiles of serum ALT had significantly greater odds of being MNHO than those in its first quartile. [Q3/Q1: adj. OR (95% CI): 3.85 (1.70 -8.71); Q4/Q1: Adj. OR (95% CI): 3.63 (1.51-8.73) ] Conclusion: This large population-based study revealed significant associations between metabolic phenotypes of obesity and ALT level. Keywords: Alanine aminotransferase, obesity, metabolic syndrome, children and adolescents, Iran